Thalassemia - Tekin Aksu; Sule Unal (Trends in Pediatrics)
Defects in protein structure or synthesis of hemoglobin are called hemoglobinopathies. Thalassemia is the most common hemoglobinopathy, and it is estimated that 5% of the world population carries at least one variant allele of thalassemia. The thalassemias can be classified as alpha or beta thalassemias. Beta thalassemia may present as silent carriers with normal hematological parameters, while beta thalassemia carriers have hypochromic microcytic anemia, associated with a high HbA2. However, patients with beta thalassemia intermedia and beta thalassemia major need transfusion intermittently or regularly and they are called non-transfusion dependent thalassemias or transfusion-dependent thalassemias, respectively. This review focuses on pathophysiology, clinical, laboratory features of thalassemias along with their treatment and follow-up.